THE ROLE OF MOTHER TONGUE LESSONS IN DEVELOPING CREATIVE THINKING IN PRIMARY SCHOOL STUDENTS - Qizi, Shermirzayeva Munira Biymirza (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to explore the role of mother tongue lessons in fostering creative thinking among primary school students, emphasizing their contribution to lifelong learning and problem-solving skills. Method: Using a qualitative descriptive approach, the research analyzes various strategies such as role-playing, collaborative projects, storytelling, discussions, and literary exercises to identify how mother tongue instruction stimulates creativity. Data were reviewed from relevant educational practices and literature to examine how linguistic familiarity, emotional connection, and teacher facilitation enhance students’ motivation and originality. Results: The findings indicate that integrating creative activities into mother tongue lessons not only strengthens vocabulary and language proficiency but also significantly enhances curiosity, imaginative thinking, and critical reasoning. Moreover, a supportive classroom environment and individualized guidance were found to be crucial in nurturing students’ creative potential. Novelty: This study highlights the unique role of native language instruction as a catalyst for creativity development, presenting it as an underexplored yet vital avenue for cultivating innovative, confident, and flexible thinkers in primary education. By positioning mother tongue lessons as a foundation for creativity, this research underscores their broader contribution to holistic student growth and future readiness.